Recent development in emerging phosphorene based novel materials: Progress, challenges, prospects and their fascinating sensing applications - Tareen, Ayesha Khan; Khan, Karim; Rehman, Sarish; Iqbal, Muhammad; Yu, Jian; Nasir mahmood; Zhou, Zewen; Yin, Jinde; Chuan li; Zhang, Han (Progress in solid state chemistry, 2022)
A monolayer of black phosphorus (BP), commonly known as phosphorene is a novel member of the two-dimensional (2D) materials family. In consequence of its “puckered” lattice structure, phosphorene has a larger surface to volume ratio than graphene and transition metal dichalcogenides (TMDCs), and has revealed some distinct benefits in sensing applications. Since, its first synthesis in 2014 by mechanical exfoliation has spurred a wave of material science research activity. Phosphorene's structure and anisotropic characteristics, with its applications in transistors, batteries, solar cells, disease theranostics and sensing has been the subject of several reviews. This pursuit has sparked a flurry of new areas of research, theoretical and experimental, targeted at technological breakthroughs. The target of this review is to explain current advances in phosphorene synthesis, properties, and sensing applications, such as gas sensing, humidity sensing, photo-detection, bio-sensing, and ion-sensing. Finally, we will discuss the present obstacles and potential for phosphorene synthesis, properties and sensing applications. [Display omitted]